lean2/tests/lean/tst6.lean.expected.out
Leonardo de Moura 4dd6cead83 refactor(equality): make homogeneous equality the default equality
It was not a good idea to use heterogeneous equality as the default equality in Lean.
It creates the following problems.

- Heterogeneous equality does not propagate constraints in the elaborator.
For example, suppose that l has type (List Int), then the expression
     l = nil
will not propagate the type (List Int) to nil.

- It is easy to write false. For example, suppose x has type Real, and the user
writes x = 0. This is equivalent to false, since 0 has type Nat. The elaborator cannot introduce
the coercion since x = 0 is a type correct expression.

Homogeneous equality does not suffer from the problems above.
We keep heterogeneous equality because it is useful for generating proof terms.

Signed-off-by: Leonardo de Moura <leonardo@microsoft.com>
2013-10-29 16:20:06 -07:00

118 lines
4.2 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

Set: pp::colors
Set: pp::unicode
Assumed: N
Assumed: h
Proved: CongrH
Set: lean::pp::implicit
Theorem CongrH {a1 a2 b1 b2 : N} (H1 : eq::explicit N a1 b1) (H2 : eq::explicit N a2 b2) : eq::explicit
N
(h a1 a2)
(h b1 b2) :=
Congr::explicit
N
(λ x : N, N)
(h a1)
(h b1)
a2
b2
(Congr::explicit N (λ x : N, N → N) h h a1 b1 (Refl::explicit (N → N → N) h) H1)
H2
Theorem CongrH::explicit (a1 a2 b1 b2 : N) (H1 : a1 = b1) (H2 : a2 = b2) : (h a1 a2) = (h b1 b2) := CongrH H1 H2
Set: lean::pp::implicit
Theorem CongrH {a1 a2 b1 b2 : N} (H1 : a1 = b1) (H2 : a2 = b2) : (h a1 a2) = (h b1 b2) := Congr (Congr (Refl h) H1) H2
Theorem CongrH::explicit (a1 a2 b1 b2 : N) (H1 : a1 = b1) (H2 : a2 = b2) : (h a1 a2) = (h b1 b2) := CongrH H1 H2
Proved: Example1
Set: lean::pp::implicit
Theorem Example1 (a b c d : N)
(H : eq::explicit N a b ∧ eq::explicit N b c eq::explicit N a d ∧ eq::explicit N d c) : eq::explicit
N
(h a b)
(h c b) :=
DisjCases::explicit
(eq::explicit N a b ∧ eq::explicit N b c)
(eq::explicit N a d ∧ eq::explicit N d c)
((h a b) == (h c b))
H
(λ H1 : eq::explicit N a b ∧ eq::explicit N b c,
CongrH::explicit
a
b
c
b
(Trans::explicit
N
a
b
c
(Conjunct1::explicit (eq::explicit N a b) (eq::explicit N b c) H1)
(Conjunct2::explicit (eq::explicit N a b) (eq::explicit N b c) H1))
(Refl::explicit N b))
(λ H1 : eq::explicit N a d ∧ eq::explicit N d c,
CongrH::explicit
a
b
c
b
(Trans::explicit
N
a
d
c
(Conjunct1::explicit (eq::explicit N a d) (eq::explicit N d c) H1)
(Conjunct2::explicit (eq::explicit N a d) (eq::explicit N d c) H1))
(Refl::explicit N b))
Proved: Example2
Set: lean::pp::implicit
Theorem Example2 (a b c d : N)
(H : eq::explicit N a b ∧ eq::explicit N b c eq::explicit N a d ∧ eq::explicit N d c) : eq::explicit
N
(h a b)
(h c b) :=
DisjCases::explicit
(eq::explicit N a b ∧ eq::explicit N b c)
(eq::explicit N a d ∧ eq::explicit N d c)
((h a b) == (h c b))
H
(λ H1 : eq::explicit N a b ∧ eq::explicit N b c,
CongrH::explicit
a
b
c
b
(Trans::explicit
N
a
b
c
(Conjunct1::explicit (a == b) (b == c) H1)
(Conjunct2::explicit (a == b) (b == c) H1))
(Refl::explicit N b))
(λ H1 : eq::explicit N a d ∧ eq::explicit N d c,
CongrH::explicit
a
b
c
b
(Trans::explicit
N
a
d
c
(Conjunct1::explicit (a == d) (d == c) H1)
(Conjunct2::explicit (a == d) (d == c) H1))
(Refl::explicit N b))
Proved: Example3
Set: lean::pp::implicit
Theorem Example3 (a b c d e : N) (H : a = b ∧ b = e ∧ b = c a = d ∧ d = c) : (h a b) = (h c b) :=
DisjCases
H
(λ H1 : a = b ∧ b = e ∧ b = c, CongrH (Trans (Conjunct1 H1) (Conjunct2 (Conjunct2 H1))) (Refl b))
(λ H1 : a = d ∧ d = c, CongrH (Trans (Conjunct1 H1) (Conjunct2 H1)) (Refl b))
Proved: Example4
Set: lean::pp::implicit
Theorem Example4 (a b c d e : N) (H : a = b ∧ b = e ∧ b = c a = d ∧ d = c) : (h a c) = (h c a) :=
DisjCases
H
(λ H1 : a = b ∧ b = e ∧ b = c,
let AeqC := Trans (Conjunct1 H1) (Conjunct2 (Conjunct2 H1)) in CongrH AeqC (Symm AeqC))
(λ H1 : a = d ∧ d = c, let AeqC := Trans (Conjunct1 H1) (Conjunct2 H1) in CongrH AeqC (Symm AeqC))